PENGARUH PENERAPAN MEDIA DIORAMA TERHADAP KECERDASAN VISUAL SPASIAL PADA ANAK USIA5-6 TAHUN DI TK PERMATA AL-ITQON PEKANBARU - Irna Chyntia Dewi; Zulkifli Zulkifli; Rita Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this study is to determine the effect of implementing diorama media to the children’s visual spatial intelligence aged 5-6 years in Permata Al-ItqonKindergarten Pekanbaru.This research is an experimental research using one group design under pre-test by using an observation sheet of spatial visual intelligence. The populations as well as samples in this study are children in class B2 as many as 20 children.The method used is pre-experiment with one group design that is experiment conducted only in one group without any comparison group.The type of instrument used in this study was by utilizing an observation guideline to record the activities that occurred during the given treatment. Based on hypothesis test results obtained that there wasan effect of the diorama media application to children’s visual spatial intelligence aged 5-6 years. Obtained t value of 13.813 with sig 0.00, due to sig <0,05, it can be concluded that there are significant differences in spatial visual intelligence in the students before and after the application of diorama media. In Hypothesis test can be seen that t calculate = 13.813> t table = 2.145. It can be interpreted that there is a significant difference of the result between pretest and posttest. The effect of implementing diorama media on children’s spatial visual intelligence aged 5-6 years in Permata Al-ItqonKindergarten Pekanbaru is 45,5%.Keywords: Diorama Media, Spatial Visual Intelligence